Abundance and seasonal activity of Haemaphysalis concinna (Acari: Ixodidae) at the border between China and Russia in Northern Inner Mongolia, China. Issue 1 (December 2016) - Meng, Hao; Xu, Shiqi; Yu, Zhijun; Li, Ningxin; Wang, Rongrong; Gao, Xiaohe; Yang, Xiaolong; Liu, Jingze
Abstract Background Haemaphysalis concinna, a three-host tick vector of several pathogens, poses a high risk to the health of humans and livestock. However, knowledge of the seasonal activities, relative density and other ecological characteristics of this tick is quite limited and fragmentary. This knowledge gap represents a bottleneck in our understanding of the health risks associated with tick-borne pathogens. Methods We conducted a two-year study from April 2012 to March 2014 in Northern Inner Mongolia situated on the China-Russia border, China, to investigate the seasonal activities and relative density of the three developmental stages ofH. concinna . During the study period, feeding ticks were removed weekly from domestic sheep and their attachment sites were recorded. Questing ticks were collected weekly from five habitats (broadleaf forest, coniferous forest, shrubs, grassland and mixed coniferous forest) using the flagging-dragging method of capture. Rodents were captured and examined on two consecutive nights each week from June to September in 2012. Results H. concinna ticks were found mainly in shrubs and grasslands habitats. Adults were encountered from February to October with the major peak occurring in June. Larvae, which were observed mainly from late April to late September, reached peak numbers in late July. Nymphs were observed mainly from March to October, and their numbers peaked in early July.H. concinna adults and nymphs were found attached to sheep and their most favored sites of attachment were the face and ears.H. concinna larvae were found on two rodent species, Apodemus peninsulae andEutamias sibiricus . Conclusion The relative density and seasonal activities ofH. concinna have been systematically reported for Northern Inner Mongolia, China. The information about the hosts infested byH. concinna and its preferred attachment sites on sheep will help efforts to control this tick and the tick-borne diseases carried by it.